Assessment of black soldier fly derived inputs and conventional fertilisers on the growth of Amaranthus aritis in a pot culture experiment - Arasu, A; Srinivasan, G; Shanthi, M; Murugan, M; Anandham, Rangasamy; Saravanan, S (Plant Science Today, 2025)
An in vitro study was conducted to evaluate the effects of various soil amendments on the growth performance and nutrient uptake of Amaranthus aritis. Five treatment conditions were evaluated, including control (Soil), soil + compost, soil + NPK, soil + compost + Black Soldier Fly (BSF) vermiwash and soil + BSF frass (15 %). Growth parameters, including crop weight, root weight, number of leaves, plant height and chlorophyll content were recorded, alongside post-harvest nitrogen, phosphorus and potassium content in both leaf and soil samples. The results revealed a significant improvement in all growth metrics with organic and integrated nutrient management treatments compared to the control. Notably, the soil + BSF frass (15 %) treatment produced the highest crop weight (16.32 g/plant), root weight (2.94 g/plant), leaf number (21/plant), plant height (54.7 cm) and chlorophyll content (4.3 mg/g FW). This treatment also yielded the highest post-harvest leaf nitrogen (4.25 %), phosphorus (0.935 %) and potassium (2.986 %) levels. These findings highlight the potential of BSF-derived amendments, particularly BSF frass, in enhancing plant growth and nutrient content, thereby offering a sustainable alternative to conventional fertilisers for leafy vegetable cultivation.